2021
DOI: 10.1007/978-3-319-70061-8_95-1
|View full text |Cite
|
Sign up to set email alerts
|

Microflora of Surface Layers in Aquatic Environments and Its Usage

Abstract: Periphytic biofilm, also known as periphyton, which is a microflora aggregate composed of heterotrophic and autotrophic microorganisms, such as microalgae, bacteria, fungi, and protozoa, ubiquitously grows at the interface of water and soil/ sediment of almost every aquatic ecosystem ranging from small ponds to large oceans, also including paddy fields (Wu 2016; Sun et al. 2021). It well reflects a critical vision of the Sustainable Development Goals that employing the ubiquitous periphytic biofilm in water di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Microorganisms are the main producers and consumers of the EPS component in periphytic biofilms; their activity will directly change the composition and content of EPS in periphytic biofilms [9]. Here we found that the microbial community of periphytic biofilms grown in paddy fields is different from those grown in natural aquatic ecosystems, which are largely dominated by various phototrophic algae [18]. Periphytic biofilms growing in paddy fields are mainly dominated by chemotrophic microorganisms, which may be a result of the abundant supply of nitrogen and phosphorus, and limited light caused by rice canopy shading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms are the main producers and consumers of the EPS component in periphytic biofilms; their activity will directly change the composition and content of EPS in periphytic biofilms [9]. Here we found that the microbial community of periphytic biofilms grown in paddy fields is different from those grown in natural aquatic ecosystems, which are largely dominated by various phototrophic algae [18]. Periphytic biofilms growing in paddy fields are mainly dominated by chemotrophic microorganisms, which may be a result of the abundant supply of nitrogen and phosphorus, and limited light caused by rice canopy shading.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maybe certain climatic factors would lead to the decreased synthesis of EPS by periphytic biofilms, resulting in the difference in the EPS content in periphytic biofilms grown in different rice planting areas. In addition, it is well known that climatic factors, such as lighting and temperature, can affect the growth of microbes thus shifting the microbial community structure in periphytic biofilms [4,18]. As prokaryotes and eukaryotes potentially showed different roles in the EPS content in periphytic biofilms, thus the climate-induced difference in the structures of prokaryotes and eukaryotes in different periphytic biofilms (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Microbes play key roles in the biogeochemistry of N in the environment (Mushinski et al, 2021; Wang et al, 2020); thus, their potential to intercept N loss and enhance N utilization efficiency is attracting increasing attention (Antonopoulos, 2010; Mooshammer et al, 2014). In nature, microorganisms usually grow in the form of microbial aggregates (Guilhen et al, 2017; Kim & Lee, 2016); for instance, periphytic biofilms are native and ubiquitous microbial aggregates in paddy fields (Sun, Gao, & Wu, 2021).…”
Section: Introductionmentioning
confidence: 99%